Β‐Enaminone Synthesis from 1, 3‐Dicarbonyl Compounds and Aliphatic and Aromatic Amines Catalyzed by Iron Complexes of Fused Bicyclic Imidazo[1, 5‐a]pyridine Derived N‐Heterocyclic Carbenes. Issue 2 (11th January 2019) - Prakasham, A. P.; Gangwar, Manoj Kumar; Ghosh, Prasenjit
Abstract : A series of Fe–NHC complexes (1 –2 )c of the fused bicyclic imidazo[1, 5‐ a ]pyridine framework of the type [CpFe(2‐R‐imidazo[1, 5‐ a ]pyridin‐3‐ylidene)(CO)2 ]BF4 {R = mesityl (1c ), n Pr (2c )} successfully carried out the synthesis of β‐enamino ketones (3 –10 ) and (17 –27 ) and β‐enamino esters (11 –16 ) and (28 –36 ) by the condensation of acyclic and cyclic 1, 3‐dicarbonyl compounds and various aliphatic and aromatic amines in the presence of light irradiation. Quite significantly, the catalytically relevant substrate adduct species of the type [CpFe(NHC)(acac)] (2e ) and the product adduct species of the type [CpFe(NHC)(β ‐ enaminone)] (2f ) of the Fe–NHC precatalyst (2c ) have been detected by mass spectrometry study. The [CpFe(2‐R‐imidazo[1, 5‐ a ]pyridin‐3‐ylidene)(CO)2 ]BF4 {R = mesityl (1c ), n Pr (2c )} complexes were obtained from their respective N –heterocyclic carbene precursors namely, the 2‐R‐imidazo[1, 5‐ a ]pyridin‐2‐ium chloride {R = mesityl (1a ), n Pr (2a )} by the reaction with CpFe(CO)2 I in the presence of KN(SiMe3 )2 followed by the salt metathesis reaction with AgBF4 . Abstract : The iron N‐heterocyclic carbene complexes derived from fused bicyclic imidazo[1, 5‐ a ]pyridine based systems successfully carried out the condensation reaction between 1, 3‐dicarbonyl compounds and various aliphatic and aromatic amines giving β‐enamino ketones and β‐enamino esters. The catalytically relevant intermediate species have been detected by ESI‐MS.